Pengaruh Budaya Organisasi dan Motivasi Kerja terhadap Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kabupaten Ciamis - Ading Rahman Sukmara; Ima Rahmawati; Ferey Herman (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
The Population and Civil Registration Office of Ciamis Regency is located in the administrative area of the Ciamis regency government. The Ciamis Regency Population and Civil Registration Office was formed through Ciamis Regency Regional Regulation No. 8 of 2016 concerning the Establishment and Structuring of Regional Apparatus and Ciamis Regent Regulation No. 48 of 2016 concerning Duties, Functions, and Work Procedures of Organizational Elements of the Population and Civil Registration Office. The object of this study is the employees of the Ciamis Regency Population and Civil Registration Office, which is 57 employees. The problems faced in this study include (1) How Organizational Culture Affects Employee Performance; (2) How does work motivation affect employee performance; (3) How the Influence of Organizational Culture and Work Motivation on Employee Performance. The research method used is a descriptive method of analysis with a quantitative approach and a correlational research design. Primary and secondary data sources with questionnaire data collection tools. Correlation data analysis technique with multiple regression. Based on the results of statistical testing, it was concluded that the variables of organizational culture and work motivation had a joint or simultaneous effect on employee performance. In this study, the employee performance variable can be explained by the variables of organizational culture and work motivation by 76%, while the rest is explained by other variables outside the model, this shows that the relationship is included in a very strong category.